Pemanfaatan dan Pengembangan Produk UMKM Berbasis Kearifan Lokal guna Meningkatan Pendapatan Masyarakat di Kepulauan Riau - Bunga Paramita; Fahranisa Azzahra; Siti Mayawi Vanesa (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2022)
Kepulauan Riau is a territory of the State of Indonesia which is located in the golden triangle of the world economy, and is located in the Exclusive Economic Zone (EEZ), the existence of the Riau Islands Province is very strategic in increasing local potential, especially the economic sector. Culture is an inseparable part of a community group. Culture is also what makes the difference between one community group and another, because the different living habits of people make the resulting culture also different. This culture is also inseparable from the Malay community in the Riau Islands province. Malay culture does not only consist of one type of culture, but Malay culture has a variety of other cultures, including dance, traditional houses, musical instruments, crafts, culinary and others. One of the existing cultures that has been passed down from generation to generation is the craft culture of the Malay community. The examples of crafts from the Malay tribal community are in the form of a Tudung Manto, Tudung Batik, Gasing, Tanjak and many other examples. However, this craft from Malay culture is expected to be able to penetrate the export market through digital export so that it can help increase the income and economy of the people in the Kepulauan Riau. In addition to culture in the form of handicrafts, the province of Riau Islands has other cultures, such as the culinary specialties of the Malay community. Culinary typical of the Kepulauan Riau, such as Otak-Otak, Deram Deram, Ikan Asap, Kue Bangkit, Gonggong and many more. One of the typical culinary delights of the Kepulauan Riau is Otak otak. However, it is rare to find media that exposes and introduces local wisdom of traditional Malay culinary in the Kepulauan Riau. Then, a part from culture in the form of handicrafts and culinary such as otak-otak, a cultur that has been developed by the government and received guidance through existing SMEs centers, too be expected can help increase the income and economy of the people in the Kepulauan Riau. By using descriptive analysis through a scientific approach with data sourced from the facts found in the research. As well as using a questionnaire have the Gform in assisting research